2017
DOI: 10.1167/iovs.16-20977
|View full text |Cite
|
Sign up to set email alerts
|

Automated Quantitation of Choroidal Neovascularization: A Comparison Study Between Spectral-Domain and Swept-Source OCT Angiograms

Abstract: PurposeTo compare the lesion sizes of choroidal neovascularization (CNV) imaged with spectral-domain (SD) and swept-source (SS) optical coherence tomography angiography (OCTA) and measured using an automated detection algorithm.MethodsPatients diagnosed with CNV were imaged by SD-OCTA and SS-OCTA systems using 3 × 3-mm and 6 × 6-mm scans. The complex optical microangiography (OMAGC) algorithm was used to generate the OCTA images. Optical coherence tomography A datasets for imaging CNV were derived by segmentin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
75
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 96 publications
(78 citation statements)
references
References 36 publications
1
75
2
Order By: Relevance
“…Previous studies have reported statistically significantly larger CNV demarcation areas for different SS-OCTA than for commercially available SD-OCTA systems. 33,34 Further, an evaluation algorithm (e.g., variable interscan time analysis) as described by Choi et al, allows the interscan time to be increased from 1.5 to 3 ms, which decreases the limits for the lowest detectable and fastest distinguishable flow and consequently reveals microvascular structures previously not seen. 35 However, these OCTA systems are not yet commercially available.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have reported statistically significantly larger CNV demarcation areas for different SS-OCTA than for commercially available SD-OCTA systems. 33,34 Further, an evaluation algorithm (e.g., variable interscan time analysis) as described by Choi et al, allows the interscan time to be increased from 1.5 to 3 ms, which decreases the limits for the lowest detectable and fastest distinguishable flow and consequently reveals microvascular structures previously not seen. 35 However, these OCTA systems are not yet commercially available.…”
Section: Discussionmentioning
confidence: 99%
“…Analyses of various SS-OCTA prototypes have already shown their superior ability regarding CNV detection compared with SD-OCTA. 33,34,36 Certain areas of the CNV lesion may not be detectable in SD-OCTA because of very slow or fast blood flow. This is not the case in ICGA, as the dye will eventually stain the whole CNV lesion during the 30 minutes of examination, independent of blood flow velocity.…”
Section: Discussionmentioning
confidence: 99%
“…SD-OCT typically uses an 800 to 900-nm wavelength source, and its scan speed ranges from 40 to 100-kHz. SD-OCT has increased sensitivity roll-off with depth as compared to SS-OCT (Miller, Roisman et al 2017, Zhang, Chen et al 2017). Also, shorter wavelengths are more prone to scattering and attenuation; thus, they penetrate into tissue less than the longer wavelengths used in the SS-OCT devices.…”
Section: Principles Of Optical Coherence Tomography Angiographymentioning
confidence: 99%
“…We used SD-OCTA systems operating at 840 nm even though light at this wavelength is greatly scattered and absorbed by the RPE complex, which can affect the ability to examine the choriocapillaris vessels. 15,16 We did not analyze the choriocapillaris vessels in this study. In addition, the clarity of the images of the choroidal vascular layer was dependent on the status of the RPE, which was affected by the stage of RP.…”
Section: 13mentioning
confidence: 99%